(3JaSjQ GdebGdI GdChdi ef GdCda GdUZQis - (3jMji Hf YOi Hf RcQjGs
(3ChdgG (B:s
(3bGd GQSWhWGdjS Gf GdfXQ ai Mb UYH ef LgI Sgd ef LgI hGdOdjd Ydi Pdc Gfg de jbOQ GMO ef GdfGS Ydi GdHdhZ ajg s
(3BNQgG (B:s
(3bGd jMji Hf YOi jfHZi Gf jYde Gf gPG GdaUd hLOg ai fbd GSMb Hf Mfjf abW hde GLOg ai GdfSN GdSQjGfjI GdfXQ ai GdYdd hGdGhGFd cdgG dYde hGMO Gh GdYdhe GcKQ efg hGMO hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B(255(1)) s
Keywords: (3GdadSaI hGdefWbs